New Composite Leading Indicators for Hungary and Poland - Harm Bandholz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
This paper presents new composite leading indicators for the two largest of the EU accession countries, Poland and Hungary. Using linear and non-linear dynamic factor models we find for both countries that a parsimonious specification, which combines national business cycle indicators,series reflecting trade volumes and supranational business expectations makes for the most reliable business cycle leaders. The composite leading indicators significantly Granger-cause GDP growth rates, while the estimated Markov-switching probabilities of being in a recessionarystate agree well with a priori determined cycle chronologies.
Keywords: C32; C53; E32; 330; Business Cycles; Composite Leading Indicators; EU Enlargement; Markovswitching; Turning Points